WISATA KULINER DURIAN DI JALAN JENDERAL SUDIRMAN KOTA PEKANBARU - Khasana, Meiriau; Yusrizal, Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Culinary tours in Indonesia are filled with various variations, one of which is processed products from durian fruit. This study aims to describe durian culinary tours on Jendral Sudirman street Pekanbaru city and find out consumers responses to durian culinary tours on Jendral Sudirman street Pekanbaru city. This research method is a quantitative method. Data collection techniques are carried out by observation, interviews, documentation and questionnaires. The results showed that the durian culinary tour was a tourist product in which there were attractions such as the taste of durian fruit which was delicious, had a soft texture, the beauty of the processed durian colors looked attractive. Accessibility to durian culinary tourism locations that are very strategic makes it easy for consumers to come and public transportation is easy to get to get to that location. And has facilities available in durian culinary tours such as parking lots, tables and chairs, wipes, hand washers, toilets and trash cans. This attraction, accessibility, and facility will be responded by consumers to find out the assessment of durian culinary tourism products.Keywords: Culinary Tourism, Attractions, Accessibility, Facilities